THE USE OF MIND MAPPING TO IMPROVE DESCRIPTIVE WRITING SKILL: A Classroom Action Research with The Students of SMP N 7 Surakarta - Julieta Tisya Majid; Sri Handayani (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2023)
This research was aimed to determine the improve students’ writing skill by using mindmapping to eighth grade students especially in class VIII B of SMP N 7 Surakarta in the2022/2023 academic year. The method used in this research was a Classroom ActionResearch (CAR). The research was conducted in two cycles. The subject was the studentsof SMP N 7 Surakarta in 2022/2023 academic year. This research used test and non-test tocollecting the data. To analize the data, this research used qualitative data and quantitativedata. The qualitative data is consisted of data collection, data reduction, data display,conclusion, and verifying. The quantitative data is consisted of mean score and t-testformula. The result of the research, it can be seen from the mean score of Pre-Test was61.34, Post-Test 1 was 71.21, and Post-Test 2 was 85.28. The t-test value of Cycle I was4.14, and the t-test value of Cycle II was 10.22. The result of the research showed that mindmapping technique can improve the students’ writing skill. It can be seen from the studentswriting achievement. It can be concluded that mind mapping technique can be improvestudents’ writing skill.Keywords: Mind Mapping, Descriptive Writing Skill, Classroom Action Research.